Cherax pulverulentus, a new freshwater crayfish (Decapoda: Parastacidae) from Southwest Papua Province, Indonesia - Patoka, Jiří; Akmal, Surya Gentha; Bláha, Martin; Kouba, Antonín (Zootaxa, 2025)
Cherax pulverulentus sp. nov. is a moderately-sized burrowing freshwater crayfish endemic to the streams west of the Ayamaru Lake in Bird’s Head Peninsula (Framu Subdistrict, Southwest Papua Province), the Indonesian part of New Guinea. Although this species has been exploited in the ornamental aquarium trade at least for 21 years, it has not been formally named until now. Its commonly used commercial names in the pet trade are: “Hoa Creek”, “Irian Jaya”, or “Blue Moon” crayfish, but these names are also used for other more bluish or pinkish species of Cherax. Cherax pulverulentus sp. nov. is genetically and morphologically most similar to Cherax pulcher Lukhaup, 2015, but both species may be distinguished by several morphological characteristics and DNA sequence divergence, which support C. pulverulentus sp. nov. as a valid species.